Legal Politics of Witness Protection Guarantee for Reporter of Election Criminal Violations as an Effort to Enforce Indonesian Election Laws - Maharani, Wianda Julita (Veteran Law Review, 2024)
This study aims to determine the urgency of providing guarantees for the protection of reporter witnesses of election criminal violations in national law. This research is a normative legal research using literature research as the data collection method. The research method used is normative juridical based on statute approach. The results of this study indicate that there is no legal guarantee for the protection of reporter witnesses of election criminal offenses as a form of lex specialis of electoral law enforcement in Indonesia. Meanwhile, the guarantee of protection of the reporter's witness is very necessary to maintain the stability of democracy in Indonesia which is characterized by the running of elections according to the principle of LUBER JURDIL. As a result, the author recommends that lawmakers formulate legal products, both in the form of laws and amendments to laws that are able to accommodate the needs of legal protection of reporting witnesses of election criminal offenses.